Studies on comparison of nano-urea and prilled urea for enhancing maize (Zea mays) growth and productivity - SATYAM RAWAT; RAJIV KUMAR SINGH; PREETI SINGH; PK UPADHYAY; KAPILA SHEKHAWAT; SEEMA SANGWAN; SUKANTA DASH; BIJAN KUMAR MONDAL; RAJAN SHUKLA (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during the rainy (kharif) season of 2022–23 at the ICAR-Indian Agricultural Research Institute, Hazaribagh, Jharkhand to assess how well nano- urea performs in maize under different field conditions and investigate its compatibility with other N sources. Results showed that root weight (fresh and dry), partial factor productivity (N, P2O5 and K2O), N concentration (grain and stover), grain yield, biological yield and harvest index of maize were all significantly affected by the application of various N rates and nano-fertilizers. The grain yield of maize was comparable to the yield obtained under RDF and 75% of the recommended N + two nano-urea sprays. These findings indicate that the concurrent use of these nano-fertilizers has the potential to reduce N fertilization by as much as 25%. Furthermore, the results highlight the prospect of augmenting biological yield of maize by incorporating 2 nano-urea sprays alongside the prescribed N quantity from prilled urea, as well as full applications of P2O5 and K2O.